The first case of a mosaic superficial epidermolytic ichthyosis diagnosed by Ultra‐Deep Sequence. Issue 11 (2nd September 2020) - Li, Yue; Cheng, Ruhong; Liang, Jianying; Yao, Zhirong; Li, Ming
Abstract: Background: Superficial epidermolytic ichthyosis (SEI), known as ichthyosis bullosa of Siemens (IBS; OMIM No. 146800) before, is a type of keratinopathic ichthyosis due to the KRT2 mutations (NM_000423.3; OMIM No. 600194). Here, we report the first case of SEI caused by a KRT2 mosaic mutation. Methods: We presented the clinical data of a 5‐year‐old Chinese boy who suffered from SEI. The histopathological examination and immunofluorescence were performed to rule out immunobullous skin diseases and diseases with subepidermal blisters. Genomic DNA samples were extracted from the lesion tissue and next‐generation sequencing was performed. We also confirmed the variant allele frequency (VAF) in different tissues by an Ultra‐Deep Sequencing technology. Results: The patient presented with blisters on the lower extremities and linear, superficially hyperkeratotic lesions. Immunofluorescence of IgG, IgA, IgM, C3, C4, and C1q were negative, and the histopathological results showed intraepidermal blisters containing lymphocytes and eosinophils. A heterozygous missense mutation, c.G1459A (p. Glu487Lys), in exon 7 of the KRT2 gene was detected at a 31.17% allele frequency. The same mutation p. Glu487Lys has been described several times in the literature. Conclusion: Thus, in our patient, the mosaic mutation explains the blaschkoid ichthyosiform phenotype. To our knowledge, this is the first case of SEI with a KRT2 mosaic mutation. Abstract : We reported the first case of a mosaic SEI caused by a somatic p.E487 K mutation of KRT2 with a severe phenotype. We also confirmed the variant allele frequency (VAF) in different tissues by an Ultra‐Deep Sequencing technology.